1984
DOI: 10.1021/bi00318a036
|View full text |Cite
|
Sign up to set email alerts
|

Topology of beef heart cytochrome c oxidase from studies on reconstituted membranes

Abstract: The orientation of purified beef heart cytochrome c oxidase, incorporated into vesicles by the cholate dialysis procedure [Carroll, R.C., & Racker, E. (1977) J. Biol. Chem. 252, 6981], has been investigated by functional and structural approaches. The level of heme reduction obtained by using cytochrome c along with the membrane-impermeant electron donor ascorbate was 78 +/- 2% of that obtained with cytochrome c and the membrane-permeant reagent N,N,N',N'-tetramethyl-p-phenylenediamine. Electron transfer from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Oxidoreductase activity of the vesicles remained unchanged after photolabeling. It was observed that centrifugation through the detergent containing sucrose gradients (Zhang et al, 1984) partially removed subunits V and XI. Therefore, parallel experiments were conducted omitting the lipid removal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidoreductase activity of the vesicles remained unchanged after photolabeling. It was observed that centrifugation through the detergent containing sucrose gradients (Zhang et al, 1984) partially removed subunits V and XI. Therefore, parallel experiments were conducted omitting the lipid removal.…”
Section: Resultsmentioning
confidence: 99%
“…After photolysis, vesicles were diluted 20-fold with 0.1 M potassium phosphate (pH 7.8) containing 1% bovine serum albumin and centrifuged at 45 000 rpm in a Beckman 60 Ti rotor for 90 min. Pellets were resuspended in 20 mM potassium phosphate (pH 7.8) containing 5% potassium cholate and loaded on a discontinuous sucrose gradient as described by Zhang et al (1984). This centrifugation procedure was carried out twice to remove excess phospholipids and label.…”
mentioning
confidence: 99%
“…Subunits IV and VI in the yeast enzyme can be dissociated from the rest of the enzyme by urea or GuHCl at concentrations below those required for denaturation of the bulk of the enzyme (Poyton & Schatz, 1975; Montgomery, unpublished results from this laboratory). Subunit Va in the beef enzyme has been shown to be largely exposed to the aqueous phase by its tryptic removal from the reconstituted enzyme complex (Zhang et al, 1984). Also, examination of the amino acid sequences of subunits Va and Vb in the beef heart enzyme indicates that they are largely water-soluble subunits (Tanaka et al, 1979) as is the case for subunits IV and VI in the yeast enzyme (Gregor & Tsugita, 1982;Maarse et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Submitochondrial particles were isolated according to Lee and Ernster (1967). Reconstitited vesicles of cytochrome c oxidase were made as described by Zhang et al (1984).…”
Section: Methodsmentioning
confidence: 99%